2020
DOI: 10.4315/jfp-20-072
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Composition and Associated Health Risk of Honey Obtained from Apiary Farms in Southeast Nigeria

Abstract: This study investigated the levels of lead, selenium, arsenic, iron, manganese, copper, zinc, chromium, cadmium and nickel in honey and their potential health risks to consumers using standard protocols. The honey samples were obtained from apiary farms at nine different locations in southeast Nigeria. They were digested at optimal conditions and analyzed using flame absorption spectrophotometer (FAAS) (Buck scientific model 210VGP, USA). The results showed that the elemental levels in the honey varied relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
2
2
0
Order By: Relevance
“…Despite having essential minerals, the honeys had heavy metals with concentrations above maximum permissible limits. Ba, Fe, Pb, Cr, Ni, Ag, Mn, Cd and As were above recommended limits similar to the reports of Obasi et al (2020) in the South east, and Odoh et al (2015) in the middle belt. This calls for further public health concern and detailed investigation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite having essential minerals, the honeys had heavy metals with concentrations above maximum permissible limits. Ba, Fe, Pb, Cr, Ni, Ag, Mn, Cd and As were above recommended limits similar to the reports of Obasi et al (2020) in the South east, and Odoh et al (2015) in the middle belt. This calls for further public health concern and detailed investigation.…”
Section: Discussionsupporting
confidence: 88%
“…Only a few countries (like Ethiopia, Ghana and Kenya) have reputable work on contaminants and nutritional composition in honey. To our knowledge, very little or no empirical research on the elemental composition of honey has been carried out in Nigeria, and only recently, Obasi et al (2020) reported the presence of heavy metals in apiary honeys from south-eastern Nigeria with Arsenic and Lead levels above recommended range in some of the samples posing potential health risk for children. Odoh et al (2015) report also covered the middle belt region of Nigeria (Taraba, Nassarawa, FCT and Abuja) con rming the presence of honeys from that region.…”
Section: Introductionmentioning
confidence: 99%
“…The LTCR value for Cd was > 1 × 10 −5 , observed in children and adults with an apiary rank of A1 > A2, while LTCR >1 × 10 −5 was recorded for Pb in adults, especially in the A2 apiary. Several studies which characterized honey by values of LCTR included amounts of between 1 × 10 −5 and 1 × 10 −4 , like those reported in this study [63,77,[93][94][95][96].…”
Section: Carcinogenic Risk (Lctr)supporting
confidence: 59%
“…Several studies which characterized honey by values of LCTR included amounts of between 1 × 10 −5 and 1 × 10 −4 , like those reported in this study [ 63 , 77 , 93 , 94 , 95 , 96 ].…”
Section: Resultsmentioning
confidence: 57%